Localization of dengue virus in naturally infected human tissues, by immunohistochemistry and in situ hybridization - Jessie, K.; Fong, M.Y.; Devi, S.; Lam, S.K.; Wong, K.T. (2004)
Dengue viral antigens have been demonstrated in several types of naturally infected human tissues, but little is known of whether these same tissues have detectable viral RNA. We studied tissue specimens from patients with serologically or virologically confirmed dengue infections by immunohistochemistry (IHC) and in situ hybridization ( ISH), to localize viral antigen and RNA, respectively. IHC was performed on specimens obtained from 5 autopsies and 24 biopsies and on 20 blood-clot samples. For ISH, antisense riboprobes to the dengue E gene were applied to tissue specimens in which IHC was positive. Viral antigens were demonstrated in Kupffer and sinusoidal endothelial cells of the liver; macrophages, multinucleated cells, and reactive lymphoid cells in the spleen; macrophages and vascular endothelium in the lung; kidney tubules; and monocytes and lymphocytes in blood-clot samples. Positive-strand viral RNA was detected in the same IHC-positive cells found in the spleen and blood-clot samples. The strong, positive ISH signal in these cells indicated a high copy number of viral RNA, suggesting replication.